Aldol‐type group‐transfer polymerization of silyl vinyl ethers using silyl perfluoroalkaneimides as nonmetal catalysts. Issue 16 (29th May 2013) - Moyori, Takaya; Hayashi, Terunari; Takasu, Akinori
ABSTRACT We investigated the catalytic activity of bis(nonafluorobutanesulfonyl)imide (Nf2NH), acting as a Brønsted acid, and its silylated imide, t‐butyldimethylsilyl nonafluorobutanesulfonylimide (Nf2NTBDMS), acting as a Lewis acid, for aldol‐type of group‐transfer polymerization (Aldol‐GTP) of silyl vinyl ethers. Aldol‐GTPs of t‐butyldimethylsilyl vinyl ether (VOTBDMS) and triethylsilyl vinyl ether (VOTES) proceeded in dichloromethane at 0 °C with benzaldehyde as the initiator. Nf2NH catalyzed the polymerization of VOTBDMS although the product poly(VOTBDMS) had a molecular weight of 2510, which was considerably smaller than that predicted by the ratio of the initial monomer to initiator concentrations, and the smaller molecular weight was a consequence of desilylation of VOTBDMS before the polymerization step. Conversely, when Nf2NTBDMS was used as the catalyst, poly(VOTBDMS) with molecular weight >16, 000 was obtained. The Nf2NTBDMS‐catalyzed polymerization was more rapid than polymerizations that used t‐butyldimethylsilyl trifluoromethanesulfonylimide, t‐butyldimethylsilyl hexafluorocycropropanesulfonylimide, or zinc bromide as the catalyst, even though the ratio of Nf2NTBDMS to the monomer was the smallest used. With VOTES as the monomer, and Tf2NTBDMS as the catalyst, a poly(VOTES) with a syndiotactic tendency (mm:mr:rr = 9:44:47) was produced. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3516–3522